How has COVID-19 impacted disability employment?. Issue 2 (April 2023) - Ne'eman, Ari; Maestas, Nicole
Abstract: Background: While the COVID-19 public health emergency has had disastrous health impacts for people with disabilities, it remains unclear what impact the associated economic recession and subsequent recovery have had on disability employment. Objective: We evaluated employment trends for people with and without disabilities over the course of the COVID-19 recession and subsequent economic recovery, both overall and by occupational category (essential, non-essential, teleworkable, non-teleworkable, frontline, non-frontline). Methods: We made use of data from the nationally representative Current Population Survey. Linear probability models were used to estimate percent changes in employment-to-population ratios and identify differences between disabled and non-disabled employment in each quarter broadly and within specific occupational categories. Results: As the COVID-19 recession began in Q2 2020, people with disabilities experienced employment losses that were proportionately similar to those experienced by people without disabilities. However, during the subsequent economic recovery, the employment rate of people with disabilities grew more quickly in Q4 2021 through Q2 2022, driven by increased labor force participation. These employment gains have been concentrated in teleworkable, essential, and non-frontline occupations. Conclusion: Our findings suggest that people with disabilities are disproportionately benefiting from the rapid recovery from the initial economic contraction at the start of the pandemic.